UiTM Pahang and FELDA: the great malay institutions / Nur Masriyah Hamzah and Shaiful Azlan Abdul - Hamzah, Nur Masriyah; Abdul, Shaiful Azlan (2015)
FELDA is always synonym with oil palm plantation and known as the world's largest oil palm plantation operator based on planted hectares. For that reason, FELDA became the most popular agency to do research amongst undergraduate students from Faculty of Plantation and Agrotechnology. Thus, a study was conducted to reveal the connectivity between these two institutions. Generally, this study was focusing towards 74 undergraduate dissertations from the Faculty of Plantation and Agrotechnology in UiTM Pahang. An approach called "mini-meta analysis" was carried out during the investigation from 2013 until 2015. This study aims to provide a preliminary exploration of how intense the relationship between UiTM Pahang and FELDA. Therefore, the main objective of this study was to analysis the dissertations of undergraduate students from Faculty of Plantation and Agrotechnology, UiTM Pahang. The tables and figures, the type of analysis used by the students, the location of study and type of study related to FELDA were identified. This study has found that the existence of substantial linked between UiTM Pahang and FELDA by having a reciprocal relationship. It also revealed that FELDA became an important platform of doing research for undergraduate students in UiTM Pahang by taking into consideration the types of respondents, number of samples and testing of the materials engaged from FELDA. Hence, evidence from this small mini-meta analysis has proven it. Moreover, this paper offers insights into how intense the relationship between UiTM Pahang and FELDA and it bridges the two important Malay institutions for the Malay people.